Manufacturing method of absorbent body

By using alternate layering method of multi-layer nonwoven fabrics and highly absorbent resins in sanitary products, the problems of heavy and uneven water absorption caused by the use of wood pulp cellulose are solved, and the high water absorption performance and low-cost production of thin sanitary products are achieved.

JP2025503290APending Publication Date: 2025-01-30LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024545200
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-11-15
Filing Date
2023-11-16
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

When using highly absorbent resin particles in existing sanitary products such as diapers and sanitary napkins, there are problems such as heavy, airtight and high cost due to the use of pulp cellulose (pulp). At the same time, reducing the use of pulp cellulose will lead to unstable fixation of water-absorbing resin and uneven absorption.

Method used

By using an alternating layer stacking method of multi-layer nonwoven fabric and highly absorbent resin, a stable absorbent layer is formed by coating the nonwoven fabric and the highly absorbent resin multiple times and crosslinking the surface and internally using a bridge polymer.

Benefits of technology

The uniform distribution and stable fixation of highly absorbent resins are achieved, and thin sanitary products are produced, which reduces production costs and improves water absorption performance and use comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503290000001_ABST
    Figure 2025503290000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an absorbent body that can contribute to making the absorbent body thinner by appropriately fixing superabsorbent resin particles within the absorbent body without using pulp, improves the filling rate by uniformly applying the superabsorbent resin, and exhibits excellent shape retention even after absorbing moisture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0153920 dated November 16, 2022 and Korean Patent Application No. 10-2023-0158380 dated November 15, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a method for producing an absorbent body. [Background technology]

[0003] Generally, sanitary products such as various diapers, sanitary napkins, and incontinence pads contain absorbents containing super absorbent polymer particles, and such absorbents generally contain pulp mainly for the purpose of properly fixing the super absorbent polymer particles while maintaining the shape of the absorbent and the sanitary product.

[0004] However, the presence of such pulp makes it difficult to make the absorbent body and sanitary products slimmer and thinner, and causes problems such as sweat seeping between the user's skin and the sanitary products, resulting in poor comfort when worn. Moreover, the need to use a large amount of the pulp, which is mainly obtained from wood, goes against the recent trend toward environmental protection, and is in fact one of the main factors that increases the manufacturing costs of the absorbent layer and sanitary products.

[0005] Therefore, many attempts have been made to reduce the amount of pulp used in the absorbent layers and sanitary products, or to provide sanitary products such as so-called pulpless diapers that do not use pulp.

[0006] However, if the amount of pulp used is reduced too much, the binding strength is low, resulting in numerous breaks in the absorbent. Furthermore, the superabsorbent resin particles are not fixed properly in the absorbent and sanitary product, so they migrate to specific parts of the absorbent during transportation of the sanitary product, causing uneven absorption performance and making it difficult to maintain the shape of the sanitary product.

[0007] Meanwhile, in sanitary products that do not use pulp, such as pulpless diapers, previously proposed, the superabsorbent resin particles are fixed mainly using a liquid adhesive composition instead of pulp, thereby making the absorbent and sanitary products thinner and slimmer, and realizing low unit prices by not using pulp. However, in conventional sanitary products, when an excessive amount of adhesive is used, there are disadvantages such as the performance of the superabsorbent resin particles and the absorbent itself containing them being reduced by the adhesive, and process troubles occurring due to the movement of the adhesive.

[0008] Conversely, when the amount of adhesive used is reduced, there is a drawback in that the superabsorbent resin particles are not fixed well in the absorbent and sanitary goods, and uneven absorption performance occurs due to particle movement, etc. In addition, the problem that the shape of the absorbent and sanitary goods cannot be well maintained after the superabsorbent resin particles absorb water cannot be solved.

[0009] Due to these problems with the conventional technology, there is a continuing demand for technological development of a manufacturing method for an absorbent body that does not use fluff pulp or uses a significantly reduced amount of fluff pulp, yet can properly fix highly absorbent resin particles in the absorbent body and sanitary product without reducing performance, and that exhibits excellent shape retention even after absorbing moisture. Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention relates to a method for manufacturing an absorbent body that can contribute to making the absorbent body thinner by appropriately fixing superabsorbent resin particles within the absorbent body without using pulp, improves the filling rate by uniformly applying the superabsorbent resin, and exhibits excellent shape retention even after absorbing moisture. [Means for solving the problem]

[0011] In order to solve the above problems, the present invention provides A first step of applying an adhesive and a superabsorbent polymer onto a first nonwoven fabric; a second step of applying an adhesive onto the superabsorbent polymer; and and a third step of attaching and sealing a second nonwoven fabric onto the first nonwoven fabric after the second step is completed. The first nonwoven fabric and the second nonwoven fabric are not napped, The adhesive is applied without a pattern. A method for producing an absorbent body is provided.

[0012] Meanwhile, the present invention provides a method for producing a nonwoven fabric by applying an adhesive and a highly water-absorbent polymer to a first nonwoven fabric in a first step; a second step of applying an adhesive onto the superabsorbent polymer; and and a third step of attaching and sealing a second nonwoven fabric onto the first nonwoven fabric after the second step is completed. The superabsorbent resin is A base resin containing an acidic group, at least a portion of which has been neutralized, comprising a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent; and The crosslinked polymer further includes a surface crosslinked layer formed on the base resin and in which the crosslinked polymer is additionally crosslinked via a surface crosslinking agent; Satisfy the following 1) to 4); A method for producing an absorbent body is provided, comprising: 1) Water retention capacity (CRC) measured by EDANA NWSP241.0.R2 (15) was 32 g / g to 40 g / g; 2) The water-soluble content is 10% by weight or less after swelling for 16 hours according to the method of EDANA NWSP270.0.R2(15); 3) The water absorption speed (vortex time) measured by the vortex method is 30 seconds or less; and 4) Bulk density measured according to EDANA NWSP251.0.R2(15) is 0.55 g / ml or more and 0.65 g / ml or less. Effect of the Invention

[0013] The absorbent body manufactured by the manufacturing method of the present invention has excellent shape retention even after absorbing water by appropriately fixing the superabsorbent polymer without using pulp, and also has excellent absorption performance. According to the manufacturing method, it is possible to manufacture a slimmer and thinner absorbent body without using pulp, and the manufacturing cost can be reduced, and the superabsorbent polymer can be fixed to reduce rewet deviation. [Brief description of the drawings]

[0014] [Figure 1] This is a cross-section of the absorbent body of Example 1, and shows an absorbent body in which a first nonwoven fabric 1, an adhesive layer 3, a first coated layer of superabsorbent resin 4, a first coated layer of adhesive 5, a second coated layer of superabsorbent resin 6, a second coated layer of adhesive 7, and a second nonwoven fabric 2 are laminated in this order. The layers 4 to 6 are called superabsorbent resin layers. [Diagram 2] This is a cross-section of the absorbent body of Example 2, and shows an absorbent body in which a first nonwoven fabric 1, an adhesive layer 3, a first coated layer of superabsorbent resin 4, a first coated layer of adhesive 5, a second coated layer of superabsorbent resin 6, a second coated layer of adhesive 7, a third coated layer of superabsorbent resin 8, a third coated layer of adhesive 9, and a second nonwoven fabric 2 are laminated in this order. The layers 4 to 8 are called superabsorbent resin layers. [Diagram 3] The figure relates to a cross section of the absorbent body of Example 3, and shows an absorbent body in which a first nonwoven fabric 1, an adhesive layer 3, a first coated layer of superabsorbent resin 4, a first coated layer of adhesive 5, a second coated layer of superabsorbent resin 6, a second coated layer of adhesive 7, a third coated layer of superabsorbent resin 8, a third coated layer of adhesive 9, a fourth coated layer of superabsorbent resin 10, an adhesive layer 11, and a second nonwoven fabric 2 are laminated in this order. The layers 4 to 10 are referred to as superabsorbent resin layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.

[0016] Although the present invention can be modified in various ways and has various forms, specific embodiments are exemplified and described in detail below. However, it is not intended to limit the present invention to the specific disclosed embodiments, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.

[0017] Furthermore, the terminology used herein is for the purpose of referring to particular embodiments only and is not intended to limit the present invention, and the singular forms used herein include the plural forms unless the language clearly indicates otherwise.

[0018] In the present invention, the terms first, second, third, etc. are used to describe various components, and the terms are used only to distinguish one component from another.

[0019] The term "polymer" or "polymeric polymer" used in the present specification means a state in which an acrylic acid monomer, which is a water-soluble ethylenically unsaturated monomer, is polymerized, and can include all water content ranges or particle size ranges. Among the above polymers, a polymer having a water content (water content) of about 40% by weight or more in a state after polymerization and before drying can be called a hydrogel polymer, and particles of such a hydrogel polymer that have been crushed and dried can be called a crosslinked polymer.

[0020] In addition, the term "superabsorbent resin particles" refers to a particulate material that includes an acrylic acid monomer having acidic groups, at least a portion of which has been neutralized, and that includes a crosslinked polymer that has been crosslinked by an internal crosslinking agent.

[0021] Also, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of which has been neutralized, or a powder-like base resin made of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, depending on the context, or is used to encompass all of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, regranulation into fine powder, drying, pulverization, classification, etc., to be in a state suitable for commercialization. Therefore, the term "super absorbent polymer" can be interpreted as including a plurality of super absorbent polymer particles.

[0022] With the increasing demand for thin and light diapers, research into pulpless diapers is underway. Pulpless diapers require that the superabsorbent polymer (SAP) can be fixed within the absorbent core of the diaper even when the pulp has been removed.

[0023] Therefore, the inventors of the present invention have been researching a method for manufacturing an absorbent body in which adhesive and superabsorbent polymer are applied in sequence several times without using pulp. It was confirmed that the absorbent body manufactured by this manufacturing method has excellent shape retention and absorption performance because the superabsorbent polymer is uniformly applied inside the absorbent body while improving the fixation rate of the superabsorbent polymer, and the filling rate is improved, and thus the present invention has been completed.

[0024] Hereinafter, the method for manufacturing an absorbent body will be described in detail step by step according to a specific embodiment of the present invention.

[0025] (First Stage) In the first stage of the method for manufacturing the absorbent body, an adhesive and a superabsorbent polymer are applied onto a first nonwoven fabric to form a superabsorbent polymer layer in which the adhesive and the superabsorbent polymer are alternately laminated, thereby fixing the superabsorbent polymer layer having absorbent properties to the nonwoven fabric.

[0026] The first nonwoven fabric has a non-napped structure, and according to a manufacturing method according to an embodiment of the present invention, even without the napped structure, the superabsorbent polymer can be fixed to the nonwoven fabric by repeatedly applying adhesive and superabsorbent polymer.

[0027] Preferably, the nonwoven fabric is not particularly limited as long as it is a nonwoven fabric that is generally used for absorbents. For example, the nonwoven fabric may be a polypropylene-based nonwoven fabric, a polyethylene-based nonwoven fabric, a polyolefin-based multi-component nonwoven fabric (e.g., a PE / PP bicomponent nonwoven fabric layer), a PLA (Poly lactic acid) / PBS (Poly Butyl Succinate) material nonwoven fabric, or other various materials. Each of these nonwoven fabrics can be directly manufactured by a conventional nonwoven fabric manufacturing method or can be commercially obtained and used, so further description thereof will be omitted.

[0028] Meanwhile, the adhesive can be applied without a specific pattern. The adhesive can be applied "without a pattern" meaning that the adhesive is applied substantially uniformly over the entire application area, or that the adhesive is applied to a specific portion of the entire application area and the remaining portion is left uncoated, and the adhesive is applied randomly over the entire application area. When the superabsorbent polymer is fixed in the core of the absorbent by applying an adhesive pattern, the pattern creates empty spaces inside the core, lowering the filling rate of the superabsorbent polymer and degrading the physical properties such as the retention capacity of the diaper. Meanwhile, when the adhesive is applied in a network form, a problem of a lower fixation rate of the superabsorbent polymer in the absorbent can occur.

[0029] The adhesive can be applied by a number of methods known to those skilled in the art. For example, the adhesive can be sprayed, rolled, or spun onto the surface of the nonwoven fabric or superabsorbent polymer. The type of adhesive is also not particularly limited as long as it is an adhesive that is typically used in absorbents. For example, the adhesive can be hydrophilic, hydrophobic, biodegradable, bioderived, or a combination thereof. Preferably, when the adhesive is applied, the superabsorbent polymer layer and the nonwoven fabric are continuous with no bond sites separating them.

[0030] On the other hand, preferably, 350 cm 2 The amount of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) applied at one time on a nonwoven fabric having an area of ​​350 cm is 0.3 to 3 g, and the total amount applied may vary depending on the number of applications. 2 The total amount of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) applied onto a nonwoven fabric having an area of ​​0.3 to 10 g may be used.

[0031] The superabsorbent resin includes a base resin including a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent, the acidic groups of which have been at least partially neutralized; and a surface crosslinked layer formed on the base resin, the crosslinked polymer being additionally crosslinked via a surface crosslinking agent.

[0032] The superabsorbent polymer may have a water retention capacity (CRC) of 32 g / g to 40 g / g as measured by EDANA NWSP241.0.R2(15). Preferably, the water retention capacity of the superabsorbent polymer may be 32 g / g or more, 33 g / g or more, or 33.4 g / g or more, and 40 g / g or less, 39 g / g or less, or 38.7 g / g or less. If the water retention capacity of the superabsorbent polymer is less than 32 g / g, there is a problem that the rewetting performance is also reduced, and if the water retention capacity of the superabsorbent polymer is more than 40 g / g, there is a problem that the production of the superabsorbent polymer is difficult.

[0033] The superabsorbent polymer may have a water-soluble component of 10% by weight or less after swelling for 16 hours, as measured by the method of EDANA NWSP270.0.R2(15).Preferably, the water-soluble component of the superabsorbent polymer may have a water-soluble component of 9% by weight or less, 8% by weight or less, or 7.7% by weight or less, and 1% by weight or more, 3% by weight or more, or 5% by weight or more after swelling for 16 hours.

[0034] The superabsorbent polymer may have a water absorption speed (vortex time) of 30 seconds or less by the vortex method. Preferably, it may be 29 seconds or less or 28 seconds or less. The smaller the water absorption speed, the better. The lower limit of the water absorption speed is theoretically 0 seconds, but may be, for example, 10 seconds or more, 15 seconds or more, 18 seconds or more, 20 seconds or more, 21 seconds or more, or 22 seconds or more. If the water absorption speed of the superabsorbent polymer exceeds 30 seconds, there is a problem that the rewetting performance is also reduced, and a superabsorbent polymer having a water absorption speed of less than 10 seconds is not only difficult to manufacture, but also has a problem of leakage because the superabsorbent polymer absorbs salt water only locally. At this time, the method for measuring the water absorption speed of the superabsorbent polymer will be described in more detail in the experimental examples described below.

[0035] The superabsorbent polymer may have a bulk density, as measured by EDANA NWSP251.0.R2(15), of 0.55 g / ml or more and 0.65 g / ml or less. Preferably, the bulk density of the superabsorbent polymer may be 0.56 g / ml or more, 0.57 g / ml or more, or 0.58 g / ml or more, and 0.63 g / ml or less, 0.62 g / ml or less, or 0.60 g / ml or less.

[0036] A high water absorption rate means that the specific surface area of ​​the particles is large, so superabsorbent resin particles with a high water absorption rate have the characteristic of having a low bulk density. If the bulk density is low, a large amount of superabsorbent resin needs to be added, which increases the production cost, so it is better to have a moderately high bulk density, but when considering the balance with the water absorption rate, the range of 0.55 g / ml to 0.65 g / ml is appropriate. If the bulk density is less than 0.55 g / ml, there is a problem of non-uniform amount of superabsorbent resin being added during the production process, and if it exceeds 0.65 g / ml, flowability may decrease.

[0037] Meanwhile, the acrylic acid monomer is a compound represented by the following Chemical Formula 1:

[0038] [Chemical formula 1] R 1 -COOM 1

[0039] In the above Chemical Formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0040] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.

[0041] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. In this case, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree can be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer may precipitate, making it difficult to smoothly proceed with polymerization, and conversely, if the neutralization degree is too low, not only the water absorption of the polymer may be greatly reduced, but also the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.

[0042] The concentration of the acrylic acid monomer may be about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition containing the raw material of the superabsorbent resin and the solvent, and may be an appropriate concentration taking into consideration the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent resin may be low, causing problems in terms of economy, and conversely, if the concentration is too high, problems may occur in the process, such as partial precipitation of the monomer or reduced efficiency in pulverizing the polymerized hydrogel polymer, resulting in reduced physical properties of the superabsorbent resin.

[0043] In addition, the term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of superabsorbent resin particles described later, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in this step is performed without distinction between the surface and the inside, but when the surface crosslinking process of the superabsorbent resin particles described later is performed, the particle surface of the finally produced superabsorbent resin has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.

[0044] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking bonds during polymerization of the acrylic unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups capable of reacting with the water-soluble substituent of the acrylic unsaturated monomer and one or more ethylenically unsaturated groups; or a crosslinking agent having two or more functional groups capable of reacting with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used.As an example, the internal crosslinking agent may be an epoxy compound.

[0045] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking during polymerization of the acrylic unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups that can react with the water-soluble substituent of the acrylic unsaturated monomer and one or more ethylenic unsaturated groups; or a crosslinking agent having two or more functional groups that can react with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used.

[0046] The internal crosslinking agent may be an epoxy compound or a polyethylene glycol-based polymer. Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth) ... acrylate, pentaerythritol tetraacrylate, and other acrylate-based compounds; ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and other epoxy-based compounds; triarylamine; propylene glycol; glycerin; or polyfunctional crosslinkers such as ethylene carbonate, which may be used alone or in combination of two or more, but are not limited thereto.

[0047] According to one embodiment, the internal crosslinking agent may be an epoxy-based compound. For example, the internal crosslinking agent may be a polyfunctional epoxy compound having a valence of 2 or more, such as ethylene glycol diglycidyl ether. In this case, the foaming agent can be stably foamed by the hydrophobic particles.

[0048] In the monomer composition, the internal crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic acid monomer. For example, the internal crosslinking agent can be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.15 parts by weight or more and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the internal crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to achieve the desired water retention ability.

[0049] The crosslinking polymerization of the water-soluble ethylenically unsaturated monomer in the presence of such an internal crosslinking agent may be carried out by thermal polymerization, photopolymerization or hybrid polymerization in the presence of a polymerization initiator and, if necessary, a thickener, a plasticizer, a storage stabilizer, an antioxidant, etc., the details of which will be described later.

[0050] In addition, the superabsorbent resin further includes a surface cross-linked layer formed by additionally cross-linking the cross-linked polymer contained in the base resin via a surface cross-linking agent on at least a part of the surface of the base resin, in order to increase the surface cross-linking density of the superabsorbent resin. When the superabsorbent resin further includes a surface cross-linked layer as described above, the superabsorbent resin has a structure in which the cross-linking density is higher on the outside than on the inside.

[0051] As the surface cross-linking agent, any surface cross-linking agent that has been used in the manufacture of conventional superabsorbent resins can be used without any particular limitation.For example, the surface cross-linking agent can include one or more selected from the group consisting of polyhydric alcohol compounds, polyfunctional epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds and alkylene carbonate compounds.

[0052] Specifically, examples of the polyhydric alcohol compound that can be used include mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.

[0053] The polyfunctional epoxy compound may be ethylene glycol diglycidyl ether or glycidol.

[0054] The polyamine compound may be ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, polyamidepolyamine, or the like.

[0055] Furthermore, the haloepoxy compound may be epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, or the like.

[0056] As the oxazoline-based compound, mono-, di- or polyoxazolidinones can be used.

[0057] As the alkylene carbonate compound, ethylene carbonate, propylene carbonate, glycerol carbonate, or the like can be used.

[0058] More specifically, the surface cross-linking agent may be one of the above-mentioned surface cross-linking agents used alone or in combination with each other. As an example, an alkylene carbonate compound such as ethylene carbonate may be used as the surface cross-linking agent.

[0059] Meanwhile, the superabsorbent polymer may contain 10% by weight or less of particles having a particle size of 710 μm to 850 μm. Also, the superabsorbent polymer may contain 10% by weight or less of particles having a particle size of 150 μm or less. The particle size of the superabsorbent polymer particles may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP220.3 method.

[0060] If the content of particles having a particle size of 710 μm to 850 μm is high, exceeding 10% by weight, the thin pulpless diaper may feel hard and have poor comfort when worn, and the water absorption rate may also decrease. Also, if the content of particles having a particle size of 150 μm or less exceeds 10% by weight, there is a disadvantage that a large amount of fine powder may cause filter clogging during processing, and the working environment may also become poor.

[0061] The superabsorbent resin may also contain hydrophobic particles. Here, hydrophobic particles refer to water-insoluble particles that have a contact angle of 50° or more with respect to water or that do not dissolve in water. Particles with a contact angle of less than 50° with respect to water and water-soluble particles may dissolve in the monomer composition in the form of an aqueous solution, making it difficult to capture bubbles generated during the polymerization process, whereas hydrophobic particles are located at the interface between the neutralization liquid and bubbles such as carbon dioxide, which exhibit hydrophobicity within the neutralization liquid, and can effectively capture and stabilize the bubbles.

[0062] Therefore, the hydrophobic particles have a contact angle with water of 50° or more. More specifically, the hydrophobic particles may have a contact angle with water of 70° or more, 100° or more, 120° or more, or 150° or more and 175° or less.

[0063] At this time, the contact angle of the hydrophobic particles can be measured by the following method. First, a coating liquid is prepared by dispersing the hydrophobic particles in a methylene chloride solvent to a concentration of 5% by weight. Next, the coating liquid is spin-coated on a wafer with no surface roughness, and then dried at room temperature to remove the remaining solvent. Then, water is dropped dropwise onto the coating layer, and the contact angle is measured, which is defined as the contact angle of each hydrophobic particle.

[0064] In addition, the hydrophobic particles have an average particle size of 0.2 μm to 50 μm, but if the average particle size of the hydrophobic particles is less than 0.2 μm, it is difficult to effectively capture bubbles generated during the manufacturing process, and uniform pores are not formed, and if the average particle size of the hydrophobic particles exceeds 50 μm, the size of the pores formed may be too large, making it difficult to improve the water absorption rate of the superabsorbent resin. Specifically, for example, the hydrophobic particles may have an average particle size (μm) of 0.5 or more, 1 or more, 2 or more, or 4 or more, and 40 or less, 35 or less, or 30 or less.

[0065] Here, the average particle size of the hydrophobic particles means D50, and the "particle size Dn" means the particle size at n% of the cumulative particle number distribution according to the particle size. That is, D50 is the particle size at 50% of the cumulative particle number distribution according to the particle size, D90 is the particle size at 90% of the cumulative particle number distribution according to the particle size, and D10 is the particle size at 10% of the cumulative particle number distribution according to the particle size. The Dn can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution. D10, D50, and D90 can be measured by calculating the particle sizes at 10%, 50%, and 90% of the cumulative particle number distribution according to the particle size in the measuring device.

[0066] Such hydrophobic particles may be one or more types selected from the group consisting of hydrophobic silica, metal salts of fatty acids having 7 to 24 carbon atoms, and hydrophobic organic particles.

[0067] Here, hydrophobic silica is a general term for silica that has a low content of silanol (-SiOH) on the surface and has a contact angle with water of 50° or more, and any hydrophobic silica known in the art can be used without limitation.

[0068] In addition, the metal salt of a fatty acid having 7 to 24 carbon atoms refers to a compound in which a metal cation is bonded in place of a hydrogen ion of a carboxyl group at the end of an unsaturated or saturated fatty acid having 7 to 24 carbon atoms in the molecule and a linear structure, and in this case, the metal salt may be a monovalent metal salt or a polyvalent metal salt having a valence of 2 or more. In this case, when the hydrophobic particles are metal salts of fatty acids having less than 7 carbon atoms, air bubbles that are ionized in an aqueous solution and generated in the form of particles cannot be captured, and when the hydrophobic particles are metal salts of fatty acids having more than 24 carbon atoms, the fatty acid chains become long and dispersion may be difficult.

[0069] Specifically, when the metal salt of the fatty acid is a monovalent metal salt, it has a structure in which one fatty acid carboxylate anion is bound to an alkali ion, which is a monovalent metal cation, and when the metal salt of the fatty acid is a polyvalent metal salt, which is divalent or higher, it has a structure in which fatty acid carboxylate anions are bound to a metal cation in the number equal to the valence of the metal cation.

[0070] In one embodiment, the hydrophobic particles may be a metal salt of a saturated fatty acid having 12 to 20 carbon atoms. For example, the hydrophobic particles may be one or more metal salts of saturated fatty acids selected from the group consisting of a metal salt of lauric acid containing 12 carbon atoms in the molecule, a metal salt of tridecylic acid containing 13 carbon atoms in the molecule, a metal salt of myristic acid containing 14 carbon atoms in the molecule, a metal salt of pentadecanoic acid containing 15 carbon atoms in the molecule, a metal salt of palmitic acid containing 16 carbon atoms in the molecule, a metal salt of margaric acid containing 17 carbon atoms in the molecule, a metal salt of stearic acid containing 18 carbon atoms in the molecule, a metal salt of nonadecylic acid containing 19 carbon atoms in the molecule, and a metal salt of arachidic acid containing 20 carbon atoms in the molecule.

[0071] Preferably, the metal salt of a fatty acid may be a metal stearate, for example one or more metal salts of stearic acid selected from the group consisting of calcium stearate, magnesium stearate, sodium stearate, zinc stearate and potassium stearate.

[0072] The hydrophobic organic particles may be one or more hydrophobic polymer particles selected from the group consisting of ethylene polymers, propylene polymers, styrene polymers, butadiene polymers, styrene-butadiene copolymers, alkyl acrylate polymers, alkyl methacrylate polymers, alkyl acrylate-acrylonitrile copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-alkyl acrylate-styrene copolymers, alkyl methacrylate-butadiene-styrene copolymers, and alkyl acrylate-alkyl methacrylate copolymers.

[0073] Meanwhile, in the first step, the adhesive and the superabsorbent polymer may be applied alternately two or more times. As an example, "application is repeated two times" means that (1) adhesive application and (2) superabsorbent polymer application are performed in the order of (1)>(2)>(1)>(2). There is no restriction on the number of applications as long as the application can be uniform and the superabsorbent polymer is fixed in the absorbent body, but preferably, the adhesive and the superabsorbent polymer may be applied alternately two or more times, or three or more times, and 10 or less times, 8 or less times, 6 or less times, or 5 or less times.

[0074] In this case, the amount of the superabsorbent polymer used in each of the two or more coating processes may be different or the same, and the amount of the adhesive used in each of the two or more coating processes may be different or the same. Preferably, the amount of the superabsorbent polymer used in each of the two or more coating processes may be the same, and the amount of the adhesive used in each of the two or more coating processes may be the same.

[0075] Meanwhile, the superabsorbent resin does not contain pulp. Since the superabsorbent resin does not contain pulp, the process of mixing with pulp is omitted from the manufacturing method, and thus a cost reduction effect can be expected.

[0076] Also, preferably, the first stage of application may be performed using only the adhesive and the superabsorbent polymer. Even if only the adhesive and the superabsorbent polymer are applied as described above, the fixing rate of the superabsorbent polymer in the absorbent body can be increased by repeated application, uniform application is possible, and the filling rate of the superabsorbent polymer can also be improved.

[0077] Preferably, the total thickness of the adhesive and the superabsorbent polymer applied in the first step and the second step described below may be 5 mm or less, 4 mm or less, or 3 mm or less. The thinner the total thickness of the adhesive and the superabsorbent polymer applied in the first step, the better the wearing comfort, but as an example, it may be 1 mm or more. If the thickness exceeds 5 mm, there is a problem that it is difficult to make the sanitary product thinner and slimmer.

[0078] Preferably, the superabsorbent polymer applied in the first step is 2 The amount of the superabsorbent polymer applied in the first step may be 110 g or more per unit area (m 2 ). Preferably, the amount of the superabsorbent polymer applied in the first step may be 110 g or more, 120 g or more, 130 g or more, 140 g or more, or 150 g or more, and may be 300 g or less, 250 g or less, 240 g or less, 230 g or less, 220 g or less, 210 g or less, or 200 g or less. 2 If the content of the superabsorbent polymer per unit area (m) is less than 100 g, not only will the absolute amount of the superabsorbent polymer be insufficient, resulting in a decrease in the absorption performance, but also in the difficulty of maintaining the shape of the absorbent core. 2 If the content of superabsorbent polymer per unit exceeds 300 g, the volume of the absorbent body increases, making it difficult to make it thinner and slimmer.

[0079] On the other hand, the fixation rate may be 90% or more, which is measured by vibrating the absorbent body in the vertical direction 100 times at a frequency of 65 times / min and an amplitude of 15 mm to measure the amount of superabsorbent polymer remaining in the absorbent body without flowing out. Preferably, the fixation rate may be 95% or more, 97% or more, 98% or more, 99% or more, or 99.1% or more, or may be 100% or less.

[0080] The absorbent body may be dyed with a dye, dried, and selectively dyed only the superabsorbent resin portion. The area of ​​the dyed portion may be measured with a color meter to determine a filling rate of 90% or more. Preferably, the filling rate is 95% or more, 97% or more, 98% or more, 99% or more, or 99.5% or more, or may be 100% or less.

[0081] (Second Stage) Once the first stage of application is completed, the last layer applied onto the first nonwoven fabric (the side opposite to the first nonwoven fabric) is a superabsorbent polymer, so in the second stage, an adhesive is applied onto the superabsorbent polymer, thereby preparing for the production of an absorbent body by subsequent attachment to a second nonwoven fabric.

[0082] The adhesive used in the second step can be the same as the adhesive used in the first step.

[0083] (Third Stage) In the third step of the method for manufacturing the absorbent body, a second nonwoven fabric is attached and sealed on the first nonwoven fabric coated with the adhesive in the second step to manufacture the absorbent body.

[0084] The second nonwoven fabric used in the third step can be made of the same material as the first nonwoven fabric used in the first step, and preferably the second nonwoven fabric is not napped.

[0085] The coating, attachment and sealing methods in each step of the manufacturing method may be performed by a number of methods known to those skilled in the art, and are not particularly limited as long as they are commonly used methods.

[0086] The present invention will be described in more detail below for a better understanding of the present invention. However, the following examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.

[0087] Manufacturing Example 1 (Step 1) 100 g of water was placed in a high shear mixer, and while stirring at 5000 rpm, hydrophobic silica with an average particle size of 0.3 μm and a contact angle with water of 130° and hydrophobic silica with an average particle size of 3 μm and a contact angle with water of 130° were gradually added while being dispersed so as to be 0.2 wt% and 2 wt% based on the total weight of the final aqueous dispersion. When the silica was completely added, the mixture was stirred at 8000 rpm at a temperature of 45° C. for 30 minutes. At this time, the pH of the obtained hydrophobic silica aqueous dispersion was 9.

[0088] (Step 2) 100 parts by weight of acrylic acid was mixed with 0.01 parts by weight of PEGDA400 (polyethylene glycol diacrylate 400) as an internal crosslinking agent and 0.1 parts by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide as a photoinitiator to prepare a monomer solution. Next, while continuously supplying the monomer solution with a metering pump, 160 parts by weight of 24% by weight sodium hydroxide aqueous solution was continuously added at the same time, and 3 parts by weight of 4% by weight sodium persulfate aqueous solution, 5 parts by weight of 4% by weight ethylene glycol diglycidyl ether (EJ1030s), 5 parts by weight of 4% by weight sodium bicarbonate aqueous solution, and 5 parts by weight of hydrophobic silica aqueous dispersion containing 0.2% by weight of hydrophobic silica having an average particle size of 0.3 μm and 2% by weight of hydrophobic silica having an average particle size of 3 μm prepared in step 1 were mixed at high speed to prepare a monomer composition. By this transfer, the monomer composition was fed into a polymerization reactor consisting of a moving conveyor belt, and UV polymerization was carried out for 3 minutes by irradiating it with ultraviolet light using a UV irradiation device, thereby producing a sheet-like hydrogel polymer.

[0089] (Step 3) The hydrogel polymer was cut into pieces with an average size of about 300 mm or less, and then fed into a crusher (equipped with a perforated plate containing a plurality of holes with a diameter of 15 mm) to cut the hydrogel. The crushed hydrogel was then dried in a dryer capable of shifting airflow up and down. Hot air at 180°C was blown in to uniformly dry the hydrogel so that the moisture content of the dried powder was about 5% or less.

[0090] (Step 4) The dried resin was pulverized in a pulverizer and then classified to obtain a base resin with a size of 150 to 850 μm. The pulverizer used was a PULVERISETTE 19 manufactured by FRITSCH. A 12 mm sieve cassette was installed in the pulverizer to perform primary pulverization of the dried hydrogel. Among the following sieves (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE), mesh numbers 24 / 32 / 48 / 100 / pan were installed in order, and the pulverized particles were placed on the top of the #24 mesh, fixed to the sieve shaker, and classified at 1.5 amplitude for 10 minutes.

[0091] [Table 1]

[0092] After the classification was completed, the resin content at the top of the #24 mesh was measured, and it was found that the particles contained more than 50% by weight of the dried hydrogel that was added.

[0093] The particles on the top of the #24 mesh were subjected to secondary crushing, and for secondary crushing, a 1.0 mm sieve cassette was installed in the crusher to crush the dried hydrogel. Sieves (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE) with mesh numbers 20 / 32 / 48 / 100 / pan were installed in sequence, and the secondary crushed particles were placed on the top of the #20 mesh, fixed to the sieve shaker, and classified at 1.5 amplitude for 10 minutes.

[0094] The weight of the particles after classification can be calculated as follows:

[0095] Particle size distribution by particle size = {(weight of sieve + dried mass after classification) - (weight of empty sieve)} / (dried mass after crushing) x 100

[0096] (Step 5) 8 parts by weight of a surface crosslinking agent aqueous solution containing 1.2 parts by weight of ethylene carbonate, 0.5 parts by weight of propylene carbonate, 0.5 parts by weight of propylene glycol, and 0.5 parts by weight of hydrophilic water-dispersed silica (snotex) was sprayed onto 100 parts by weight of the classified base resin powder, and the mixture was stirred at room temperature to distribute the surface crosslinking liquid evenly on the base resin powder. Next, the base resin powder mixed with the surface crosslinking liquid was placed in a surface crosslinking reactor to carry out a surface crosslinking reaction.

[0097] In the surface crosslinking reactor, the base resin powder was gradually heated from an initial temperature of about 80°C, and was operated so as to reach a maximum reaction temperature of 190°C after 30 minutes. After reaching the maximum reaction temperature, the reaction was continued for an additional 15 minutes, and then a final superabsorbent resin sample was taken. After the surface crosslinking process, the superabsorbent resin of Example 1 having a particle size of 150 μm to 850 μm was produced by classifying the particles using a standard mesh sieve according to the ASTM standard.

[0098] Example 1 On a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 1 with a size of 350 mm x 100 mm, 0.4 g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer, 3) was uniformly applied using a hot melt sprayer, and then 6 g of the superabsorbent resin prepared in the above preparation example was uniformly applied at a feed rate of 2 g / s to prepare a first coating layer of superabsorbent resin 4. 0.4 g of adhesive was applied thereon to prepare a first coating layer of adhesive 5. Thereafter, the manufacturing process of the first coating layer of superabsorbent resin 4 and the first coating layer of adhesive 5 was repeated once more to prepare a second coating layer of superabsorbent resin 6 and an adhesive layer (second coating layer of adhesive 7), and then a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 2 was attached to prepare an absorbent. The amount of adhesive used in each adhesive layer was the same at 0.4 g, and the amount of superabsorbent polymer used in each superabsorbent polymer layer was the same at 6 g.

[0099] Example 2 On a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 1 having a size of 350 mm x 100 mm, 0.3 g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer, 3) was uniformly applied using a hot melt sprayer, and then 4 g of the superabsorbent resin prepared in the above preparation example was uniformly applied at a feed rate of 2 g / s to prepare a first coating layer 4 of superabsorbent resin. 0.3 g of adhesive was applied thereon to prepare a first coating layer 5 of adhesive. Thereafter, the manufacturing process of the first coating layer 4 of superabsorbent resin and the first coating layer 5 of adhesive was repeated two more times to prepare a second coating layer 6 of superabsorbent resin, a second coating layer 7 of adhesive, a third coating layer 8 of superabsorbent resin, and an adhesive layer (third coating layer 9 of adhesive), and then a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 2 was attached to prepare an absorbent. The amount of adhesive used in each adhesive layer was the same at 0.3 g, and the amount of superabsorbent polymer used in each superabsorbent polymer layer was the same at 4 g.

[0100] Example 3 On a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 1 measuring 350 mm x 100 mm, 0.24 g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer, 3) was uniformly applied using a hot melt sprayer, and then 3 g of the superabsorbent resin prepared in the above Preparation Example was uniformly applied at a feed rate of 2 g / s to prepare a first coating layer 4 of superabsorbent resin. 0.24 g of adhesive was uniformly applied thereon to prepare a first coating layer 5 of adhesive. Thereafter, the manufacturing process of the first coated layer of superabsorbent resin 4 and the first coated layer of adhesive 5 was repeated three more times to manufacture the second coated layer of superabsorbent resin 6, the second coated layer of adhesive 7, the third coated layer of superabsorbent resin 8, the third coated layer of adhesive 9, the fourth coated layer of superabsorbent resin 10 and the adhesive layer 11, and then a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 2 was attached to manufacture an absorbent. The amount of adhesive used in each adhesive layer was the same at 0.24 g, and the amount of superabsorbent resin used in each superabsorbent polymer layer was the same at 3 g.

[0101] Comparative Example 1 A mixture of 12 g of the superabsorbent resin of Preparation Example 1 and 5 g of pulp uniformly mixed with air in a chamber was evenly applied to the center of a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 1 having a size of 350 mm x 100 mm. Then, 1.2 g of adhesive was evenly applied with a hot melt sprayer to the space in the frame except for the part where the mixture of superabsorbent resin and pulp was placed on the first nonwoven fabric, and a second nonwoven fabric was attached to produce an absorbent body.

[0102] Comparative Example 2 0.6g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer) was uniformly applied onto a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) measuring 350mm x 100mm using a hot melt sprayer, and then 12g of the superabsorbent resin prepared in the above Preparation Example was uniformly applied at a feed rate of 2g / s to prepare a superabsorbent resin coating layer. 0.6g of adhesive was uniformly applied thereon to prepare an adhesive layer, and then a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) was attached to prepare an absorbent.

[0103] Experimental Example For the absorbents of Examples 1 to 3 and Comparative Examples 1 and 2, the fixation rate and rewet property of the superabsorbent resin in the absorbent were measured and the results are shown in Table 1 below.

[0104] (1) Fixation rate of superabsorbent resin in absorbent body (% by weight) The fixation rate of the superabsorbent polymer in the nonwoven fabric was determined by testing the amount of superabsorbent polymer in the core of the nonwoven fabric that flowed out. The absorbent bodies of the above examples and comparative examples were vibrated, and the amount of superabsorbent polymer that did not flow out and remained in the absorbent body was measured and expressed as a percentage. The vibration was carried out under the conditions that the absorbent body was fixed 1 cm from the top end to a vibration device (device name: BLM512OHP-100S, manufacturer: Oriental Motor) and then vibrated up and down at a frequency of 65 times / min, with an amplitude of 15 mm, 100 times.

[0105] The fixation rate was calculated by (W1 / WO) x 100, where WO is the weight of the absorbent body before vibration and W1 is the weight of the absorbent body after vibration. This makes it possible to know the degree to which SAP has been removed from the absorbent body due to vibration, and so this value is used as an index to confirm the degree to which SAP is fixed to the absorbent body.

[0106] (2) Filling rate of superabsorbent resin (%) The filling rate of the superabsorbent polymer means the ratio of the area of ​​the superabsorbent polymer to the area of ​​the absorbent body, and is measured as follows.

[0107] The absorbent was dyed with a dye (product name: FD&C BLUE NO.1 POWDER, manufacturer: SENSIENT) and then dried. After confirming that only the superabsorbent resin portion was selectively dyed, the area of ​​the dyed portion was measured with a color meter (instrument name: Labscan XE, manufacturer: Hunter lab) under the conditions of a spectral range of 400nm~700nm and a wavelength resolution of <3nm.

[0108] (3) Rewet property (Rewet, g) The rewetting properties of the absorbent bodies of the Examples and Comparative Examples under non-pressurized / pressurized conditions were evaluated by the following method.

[0109] Two minutes after injecting 85 mL of 0.9 wt % sodium chloride aqueous solution (physiological saline) into the center of each absorbent (size 350 mm x 100 mm x 3 mm), a paper of size 300 mm x 90 mm (300 gsm filter paper (S-300, Korea Filter Paper), approximately 1.5 g (W6 (g)) per sheet) was placed. Two minutes later, the amount of salt water that had seeped out of the absorbent into the paper was measured, and the paper was removed. 15 minutes after the injection of the physiological saline, a weight was placed on the absorbent, and 85 mL of physiological saline was additionally injected into the center of the absorbent at the same position while applying a pressure of 0.42 psi. After 15 minutes, the weight placed on the absorbent was removed for a while, and new paper (300 gsm filter paper (S-300, Korea Filter Paper), approximately 1.5 g (W6 (g)) per sheet) was placed on the absorbent, and the weight was placed on the paper again to position the paper between the absorbent and the weight. After 2 minutes, the amount of salt water that had seeped out from the absorbent into the paper was measured, and the rewet amount (g) was calculated according to the following formula 1.

[0110] [Formula 1] Rewet amount (g) = (W4(g)-W5(g)) + (W6(g)-W5(g))

[0111] In the above formula 1, W4(g) is the weight of the paper that absorbs the liquid that seeps out of the absorbent for 2 minutes 2 minutes after saline is injected into the absorbent without pressure, W5(g) is the initial weight of the paper, and W6(g) is the weight of the paper that absorbs the liquid that seeps out of the absorbent for 2 minutes under a load (0.42 psi) after saline is injected into the absorbent without pressure and under pressure.

[0112] [Table 2]

[0113] According to Table 1, the amounts of adhesive and superabsorbent polymer used in each comparative example and Examples 1 to 3 were all the same, but when the number of applications was two or more, the fixation rate of the superabsorbent polymer in the absorbent was excellent at 99% or more, and it was confirmed that the rewetting properties were also excellent the more the number of applications was two or more. [Explanation of symbols]

[0114] 1: 1st nonwoven fabric 2:Second nonwoven fabric 3: Adhesive layer 4: First coating layer of superabsorbent resin 5: First layer of adhesive 6: Second coating layer of highly absorbent resin 7: Second layer of adhesive applied 8: Third coating layer of highly absorbent resin 9: Third layer of adhesive 10: Fourth coating layer of highly absorbent resin 11: Adhesive layer

Claims

1. A first step of applying an adhesive and a superabsorbent polymer onto a first nonwoven fabric; A second step of applying an adhesive onto the superabsorbent polymer; and A third step of attaching and sealing a second nonwoven fabric onto the first nonwoven fabric after the second step is completed; The application of the adhesive and the highly water-absorbent polymer in the first step is repeated alternately two or more times; The first nonwoven fabric and the second nonwoven fabric are not napped, The adhesive is applied without a pattern. A method for manufacturing an absorbent body.

2. The superabsorbent resin does not contain pulp. A method for producing the absorbent body according to claim 1.

3. The total thickness of the adhesive and the superabsorbent resin applied in the first and second steps is 5 mm or less. A method for producing the absorbent body according to claim 1.

4. The superabsorbent resin applied in the first step is applied to the surface of the 2 ) containing 100 g or more of a superabsorbent polymer, A method for producing the absorbent body according to claim 1.

5. The first stage application is done with just adhesive and superabsorbent polymer. A method for producing the absorbent body according to claim 1.

6. The absorbent body has a fixation rate of 90% by weight or more, which is measured by vibrating the absorbent body in an up-and-down direction 100 times at a frequency of 65 times / min and an amplitude of 15 mm to measure the amount of superabsorbent polymer remaining in the absorbent body without flowing out, The absorbent body is dyed with a dye and then dried to confirm that only the superabsorbent resin portion is selectively dyed. The area of ​​the dyed portion is measured with a color meter to determine a filling rate of 90% or more. A method for producing the absorbent body according to claim 1.

7. The superabsorbent resin is A base resin containing an acidic group, at least a portion of which has been neutralized, comprising a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent; and The crosslinked polymer further includes a surface crosslinked layer formed on the base resin and in which the crosslinked polymer is additionally crosslinked via a surface crosslinking agent; Satisfy the following 1) to 4); A method for producing the absorbent body according to claim 1: 1) Water retention capacity (CRC) measured by EDANA NWSP241.0.R2 (15) is 32 g / g to 40 g / g; 2) The water-soluble component measured after swelling for 16 hours according to the method of EDANA NWSP270.0.R2(15) is 10% by weight or less; 3) A water absorption rate (vortex time) of 30 seconds or less by the vortex method; and 4) The bulk density, as measured by EDANA NWSP251.0.R2(15), is 0.55 g / ml or more and 0.65 g / ml or less.

8. A first step of applying an adhesive and a superabsorbent polymer onto a first nonwoven fabric; A second step of applying an adhesive onto the superabsorbent polymer; and A third step of attaching and sealing a second nonwoven fabric onto the first nonwoven fabric after the second step is completed; The superabsorbent resin is A base resin containing an acidic group, at least a portion of which has been neutralized, comprising a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent; and The crosslinked polymer further includes a surface crosslinked layer formed on the base resin and in which the crosslinked polymer is additionally crosslinked via a surface crosslinking agent; Satisfy the following 1) to 4); Manufacturing method of absorbent body: 1) Water retention capacity (CRC) measured by EDANA NWSP241.0.R2 (15) is 32 g / g to 40 g / g; 2) The water-soluble component measured after swelling for 16 hours according to the method of EDANA NWSP270.0.R2(15) is 10% by weight or less; 3) A water absorption rate (vortex time) of 30 seconds or less by the vortex method; and 4) The bulk density, as measured by EDANA NWSP251.0.R2(15), is 0.55 g / ml or more and 0.65 g / ml or less.

Citation Information

Patent Citations

  • Absorbent structure, its production process, and absorbent article comprising said absorbent structure

    JP2003290290A

  • Absorber and absorbent article comprising the same

    JP2015100611A

  • Method for preparing super absorbent polymer

    WO2022154566A1